SERVICE INDUSTRIES INNOVATIVE DEVELOPMENT BASED ON INTEGRATION FORMS OF BUSINESS - Yulia V. Gladkova; Magomed G. Magomedov (Advanced Engineering Research)
The possibility of innovation implementation at the service rendering enterprises with integration forms of business is considered. Application characteristics of such integration forms as consulting, leasing, technoparks, franchising and joint enterprise are analysed.